2021
DOI: 10.3390/dj9010009
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Effects of Secreted Factors from Periodontal Ligament Stem Cells

Abstract: Periodontal disease is a chronic inflammation of tooth-supporting tissues, and the destruction of these tissues results in tooth loss. Regeneration of periodontal tissues is the ultimate goal of periodontal treatment. We previously reported that transplantation of conditioned medium (CM) of periodontal ligament stem cells (PDLSCs) demonstrated the enhancement of periodontal tissue regeneration, compared to CM from fibroblasts (Fibroblast-CM). We hypothesized that the angiogenic effects of PDLSC-CM might partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The oriented periodontal ligament fibers must then be attached to newly generated alveolar bone and cementum tissue, which is one of the most challenging processes in periodontal regeneration [115]. Numerous groups have widely discussed the significant potential of periodontal regeneration with remarkable clinical success thru mechanisms of regeneration for bone, cementum, and PDL via mobilization of endogenous stem cells from their niche areas, transplantation of exogenous stem cells targeting periodontal defects, or growth/angiogenic factor-mediated regenerative modulation [115][116][117]. Numerous mesenchymal stem cell (MSC) types persist and are responsible for tissue homeostasis, acting as a reservoir of renewable stem/progenitor cells to produce other essential cells throughout adulthood [118].…”
Section: Regenerative and Stem Cell Modulationmentioning
confidence: 99%
“…The oriented periodontal ligament fibers must then be attached to newly generated alveolar bone and cementum tissue, which is one of the most challenging processes in periodontal regeneration [115]. Numerous groups have widely discussed the significant potential of periodontal regeneration with remarkable clinical success thru mechanisms of regeneration for bone, cementum, and PDL via mobilization of endogenous stem cells from their niche areas, transplantation of exogenous stem cells targeting periodontal defects, or growth/angiogenic factor-mediated regenerative modulation [115][116][117]. Numerous mesenchymal stem cell (MSC) types persist and are responsible for tissue homeostasis, acting as a reservoir of renewable stem/progenitor cells to produce other essential cells throughout adulthood [118].…”
Section: Regenerative and Stem Cell Modulationmentioning
confidence: 99%
“…As a type of MSCs isolated from periodontal tissues, hPDLSCs have multiple characteristic advantages. Studies have indicated that PDLSCs can differentiate into periodontal tissue-forming cells, such as cementoblasts, osteoblasts, and fibroblasts [17]. Additionally, in vivo studies have demonstrated successful periodontal tissue regeneration after transplanting hPDLSCs into alveolar defects [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that PDLSCs can differentiate into periodontal tissue-forming cells, such as cementoblasts, osteoblasts, and fibroblasts [17]. Additionally, in vivo studies have demonstrated successful periodontal tissue regeneration after transplanting hPDLSCs into alveolar defects [17]. In addition, hPDLSCs reveal robust self-renewal ability which is higher than that of hBMSCs and human dental pulp stem cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a bacterially-induced chronic inflammatory disease of the periodontium [1]. The accumulation of dental plaque microorganisms can result in the progressive and irreversible destruction of tooth-supporting tissues, including gingiva, periodontal ligament, cementum, and alveolar bone.…”
Section: Introductionmentioning
confidence: 99%